Inclusive and Implementable Legal Rules for E-Commerce: A Comparative Study of Indonesia and Vietnam - Bich, Ngoc Nguyen Thi; Nguyen, Phan Quoc (UI Scholars Hub, 2020)
Both Vietnam and Indonesia have large populations that promise major markets for e-commerce. The two nations record high internet coverage and large numbers of social media users. Recently, the countries have been trying to support e-commerce with new legal rules. In November 2019, Indonesia’s government introduced Government Regulation No. 80 of 2019 on Trading through Electronic Systems (GR 80, 2019). GR 80 requires e-commerce businesses to obtain business licenses, report taxes, and preserve consumer protections and rights. Similarly, Vietnam has issued a number of resolutions and guidelines since its Decree on E-Commerce in 2013 (Decree No. 52/2013/NĐ-CP). While these legal documents cover nearly all aspects of e-commerce, little of their implementability and inclusiveness has been studied. Using the individualized comparison methodology and case studies, the authors analyze the legal rules in the two countries and discover that (i) the e-commerce regulations in both countries lack implementability in terms of connection and interest among stakeholders, (ii) the regulations are implementable for big businesses with formal websites but pose a significant burden for smaller businesses, which ultimately means the lack of inclusiveness. It is recommended for both to work hard and efficiently to set up their immediate response schemes, cooperatively, to expand the participation of small online businesses and multiple other stakeholders. A strategy of cross-border collaboration to build trust in e-commerce for business owners could be studied in the future.